(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Introduction: Pregnancies complicated by threatened abortion constitute a risk group requiring careful obstetric and perinatal supervision and follow-up. Objective: The purpose of this study was to evaluate the risk factors and adverse pregnancy outcomes with threatened abortion. Methods: The prospective study was conducted in Obstetrics and Gynecology Department in Dhaka National Medical College Hospital from 1st July, 2011 to 31st December, 2013. Pregnant women presenting with per vaginal bleeding admitted before 24 weeks were included in this study group. Diagnosis of threatened abortion was confirmed from history, clinical examination & ultrasonic finding of alive fetus. We followed up all the women from their first appointment until delivery and outcomes were determined. Results: In this study 69% pregnant woman with threatened abortion were multigravida. Out of 100 pregnant women, 32 cases of pregnancy ended with abortion and rest 68 cases could continue pregnancy. Among the 68 cases, 57.35% neonate were pre-mature, 54.41% low birth weight, 17.65% neonate presented with respiratory distress syndrome and 13.23 % intra uterine growth retardation and 4.41% developed intra uterine death. Ultrasonographic study of pregnant women showed, 19% patients ended with incomplete abortion and 13% missed abortion. Among the 68 cases 13.23% were placenta praevia and 7.35% were plaecental abruption. Conclusion: Threatened abortion was associated with an increased incidence of adverse pregnancy outcomes and most commonly associated with abortion, pre-maturity, low birth weight, and intra uterine growth retardation and intra uterine death. Pregnancy with threatened abortion who continued had increased risk of low lying placenta, placenta praevia, and placental abruption. J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 57-60